The concept and types of subjects of countering offenses in the entrepreneurial sphere - V. M. Vasyliev (Bulletin of Kharkiv National University of Internal Affairs)
Theoretical approaches to the definition of the notion of the subject of counteraction to offenses are described. For this purpose, the notion of the subject of management, the subject of policing was established. The notion of a subject of an offense in the sphere of entrepreneurship is defined: a system of state and non-state bodies, public organizations, social groups and citizens whose activities are focused on eliminating the causes and conditions that give rise to and provoke offenses in the sphere of economic commercial activity (entrepreneurship), preventing these offenses from different stages of incorrect behavior of participants of relations in the field of entrepreneurship, as well as bringing them to the legal first responsibility.